The janus face of citizenship and citizenship education: the legal and sociological endless contestation - a case of Malaysia - Nur Atiqah Tang Abdullah,; Anuar Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2020)
As a cultural discourse, the problematic conception of citizenship is a product of social fragmentation in Malaysia. Citizenship can carry two meanings - legal and sociological. The legal simply refers to a subject’s right and duties to be recognized as a legally permanent inhabitant of a state. Secondly, the development of citizenship, understood in sociological terms, would involve a transformative process in which individuals come to see themselves as part of a wider citizen body, to which they owe obligations involving duties as well as having rights. The objective of this paper is to pull together citizenship and education as central themes, not legal but the sociological aspects, with the ‘nation-of-intent’ as a conceptual framework. Nevertheless, the present effort of citizenship education in Malaysia is based on a particular form of ‘nation-of-intent’ (Bangsa Malaysia). The concept of citizenship and citizenship education in Malaysia is prompting only one form of ‘nation-of intent’ available in the country. An implication of it is that the concept of citizenship and thus, nation building in Malaysia is still fraught with confusion. The presence of plurality of ‘nation-of-intent’ in contemporary Malaysia demonstrates the fact that dissenting voices are present and heard, within and without government.